PERANCANGAN SISTEM INFORMASI PENDATAAN MASYARAKAT BERBASIS WEB DI KELURAHAN BONDONGAN MENGGUNAKAN METODE WATERFALL - Mutahari, M Irgi; Setyono, Setyono; Rini, Aisah (IKRA-ITH Informatika : Jurnal Komputer dan Informatika, 2026)
Community data collection in Bondongan Subdistrict is still carried out manually using physical documents and Microsoft Excel, causing problems such as duplicate data, difficult data retrieval, delayed updates, and risks of archive loss. This study aims to design and develop a web-based community information system that supports recording, managing, searching, and presenting population data more effectively, efficiently, and systematically. Data were collected through observation, interviews, and literature study, while the system development used the Waterfall model. The system was developed using PHP with the Laravel framework and MySQL database. The design covered requirements analysis, process flows, database design, and user interface design. The resulting web-based information system integrates resident, newcomer, death, and user data management. Black Box Testing showed that the main functions, including login, adding, editing, deleting, searching, and presenting data, operated according to the requirements. Usability assessment also indicated that users considered the system easy to use, fast, simple in appearance, and helpful in improving administrative efficiency. Keyword : Information System, Community Data Collection, Web, Waterfall, Laravel